Penal Policy of Corporate Social Responsibility in the Government Regulation of the Republic of Indonesia Number 47 Of 2012 - I Nyoman Dena Asa (Jurnal Hukum Prasada, 2018)
The Corporate Social Responsibility stipulated in Act number 40 of 2007 concerning Limited Liability Companies and its Sanctions is regulated in the government regulation of Republic of Indonesia no. 47 of 2012 concerning Social and Environmental Responsibility. This aspect of law is the concerned issues in the present study, and thus the study highlights: 1) the regulation of corporate social responsibility within the Government Regulation of the Republic of Indonesia no. 47 of 2012 on Social and Environmental Responsibility of limited liability companies; 2) the conceptualization of penal in the Government Regulation of the Republic of Indonesia no. 47 of 2012 on Social and Environmental Responsibility of limited liability companies. The type of research used in this study is normative legal research, wherein the study is focused on an inventory of positive law, legal principles and doctrines, legal findings in the cases of concreto, systematic law, level of legal synchronization, legal comparison, and legal history. The materials used are primary materials, secondary materials and tertiary materials, which are analyzed by descriptive technique, comparative technique, evaluative technique, argumentative technique, and interpretive technique. The results of the study show that the regulation of corporate social responsibility in the Government Regulation of Republic of Indonesia no. 47 of 2012 is not in accordance with the provisions of article 74 paragraph 3 concerning Sanctions for Corporate Social Responsibility as stipulated in the Government Regulation of the Republic of Indonesia number 47 of 2012 concerning social and environmental responsibilities. Other fact is, a concept or draft regarding more stringent and coercive sanctions, such as criminal law sanctions is firmly necessary for the sake of legal certainty provision for the people’s welfare.